Analisis Data Penelitian Menggunakan Perangkat Lunak Excel - R. Rusli; S. Suradi; Abdul Rahman; Said Fachry Assagaf; H. Hastuty (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2021)
Data analysis is an absolute step in quantitative research, the teacher's lack of understanding in conducting data analysis has an impact on the teacher's lack of enthusiasm in conducting research and writing scientific articles. This data analysis training uses excel software. Partners of the Community Partnership Program (PKM) are mathematics teachers who join the Bantaeng district MGMP. This training is carried out offline at SMPN 3 Bantaeng Regency. This training aims to help teachers to be skilled in statistical data processing, understand the steps in conducting research with quantitative data. Passion for writing scientific articles for publication in journals. Through this training, it is hoped that these teachers will be able to process raw research data using excel software and interpret the output. This training is held in the form of material presentation, hands-on practice with excel software, and `task work'. The results achieved are 1) Teachers are skilled at processing research data using excel software, 2). Teachers better understand the steps in conducting research, 3). Able to write scientific articles properly and correctly.